2019
DOI: 10.1253/circj.cj-18-0662
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of β-Blocker Dose After Acute Myocardial Infarction

Abstract: different doses of β-blockers, and no large-scale studies have addressed this issue. Given that the guidelines do not refer to specific β-blockers or their doses, contemporary practice has been based on β-blocker doses evaluated in the previous trials. On meta-regression analysis, the clinical benefits of B eta-blockers competitively inhibit circulatory catecholamine effects and decrease heart rate and myocardial contractility, thereby reducing myocardial oxygen demand. Previous randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
0
24
0
5
Order By: Relevance
“…The study population was enrolled from the Korea AMI registry (KAMIR)-National Institutes of Health (NIH) registry. The design of KAMIR study has been described in our previous studies [ 8 , 9 ] and the details of the registry can be found at the KAMIR website ( http://www.kamir.or.kr ). Briefly, it is a prospective, multicenter online registry designed to reflect the “real world” practice in a series of Korean AMI patients since November 2005 to investigate the current clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was enrolled from the Korea AMI registry (KAMIR)-National Institutes of Health (NIH) registry. The design of KAMIR study has been described in our previous studies [ 8 , 9 ] and the details of the registry can be found at the KAMIR website ( http://www.kamir.or.kr ). Briefly, it is a prospective, multicenter online registry designed to reflect the “real world” practice in a series of Korean AMI patients since November 2005 to investigate the current clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Оптимальная продолжительность терапии БАБ является предметом обсуждения. В настоящее время нет убедительных свидетельств пользы продолжения рутинного применения БАБ через 1 год после ИМ у больных без хронической сердечной недостаточности со сниженной ФВ ЛЖ (исследования в этой области продолжаются) [167,168,169]. Больные с сердечной недостаточностью (СН) или сниженной фракцией выброса левого желудочка (<40%) должны принимать БАБ постоянно.…”
Section: блокаторы бета-адренергических рецепторов (баб)unclassified
“…the hemodynamic effects of β-blockers are considered as dose dependent, observational studies reported that patients who had had AMI were being treated with lower doses of β-blockers than that used in clinical trials (Table). [6][7][8][9][10] The discrepancy between the target dose and prescribed dose in the real-word patients is perhaps due to the adverse effects of β-blockers such as hypotension, bradycardia, coronary spasm, fatigue, depression, and metabolic disorders. 11…”
Section: Editorialmentioning
confidence: 99%